The Costa Rican intelligentsia, its mission and its unfolding. The case of the novel Elvira (1940) and the eponymous film (1955) - Salas Murillo, Bértold (2022)
The novel Elvira (1940), by Moisés Vincenzi, and its film adaptation (1955), produced by Carlos Alfaro McAdam, offer through Alberto Manara Bassi, the protagonist of both stories, a representation of the Costa Rican intellectual of the mid-twentieth century. These representations, one before and one after the founding of the Second Republic in 1949, include positions regarding the homeland, ethnicity, social classes and gender that can be linked to the historical moment of their production. On the other hand, the specular game by which the ideas and writings of the fictional subject Manara Bassi (who takes the name of Mariano González) and the author Vincenzi, known mainly for his philosophical work, coincide, turn the novel and the film into a way to examine the aspirations, concerns and contradictions of a sector of the national intelligentsia of the period.